DAMPAK BELANJA MODAL PEMERINTAH DAERAH TERHADAP KESEJAHTERAAN MASYARAKAT STUDI KASUS: PEMERINTAH KABUPATEN/KOTA SELURUH INDONESIA TAHUN 2011-2015 - Riya Dwi Handaka (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2018)
There are many ways for region to raise its economic growth and welfare. Through of accuracy of expenditures, regions can objectify their vision and goals to growth their economics and welfare. On this research aims to examine the effects of capital expenditures on welfare indicators. We use secondary data by using all of  local governments in Indonesia as research sample. There is variable capital expenditures of local governments as an exogenous variable, while the Human Development Index, labor absorption, and poverty level as an endogenous variable. This study uses panel data which combines time series data and cross section. These data were analyzed using regression with Eviews program. The results with significance level α = 0.05 showed that all hypothesis are accepted. Its proved, that capital expenditures have effects positive significantly on the Human Development Index and labor absorption, and have effects negative significantly on poverty level.